A capacidade intrínseca para o exercício físico modula a neuroplasticidade dopaminérgica induzida pelo treinamento físico aeróbico - Patricia da Conceicao Rocha Rabelo (2017)
The aim of the present study was to evaluate whether the intrinsic capacity for physical exercise influences the dopaminegic neuroplasticity induced by aerobic physical training. Initially, male Wistar rats were submitted to 3 progressive exercise tests (PET). Based on previous data of frequency distribution histogram [210 animals submitted to PET, average TE (averageTE) = 41 min, standard deviation (SD) = 16.1 min] (RABELO et al., 2015), the animals in this study were classified as low-performance (LP), standard-performance (SP) and high-performance (HP) according to the following criteria: LP: animals with TE < averageTE minus 1 SD (TE < 24.9 min), HP: animals with TE > averageTE plus 1 SD (TE > 57.1 min). All the other rats were classified as SP. After initial classification, each group was subdivided into two experimental situations: sedentary (SED) and trained (TR). Aerobic physical training lasted six weeks and was performed 5 times/week. Before and after training, oxygen uptake (VO2) was measured during a progressive exercise protocol and based on results, the mechanical efficiency (ME) was calculated. After six weeks, the animals were euthanized. In the caudate-putamen (CPu) were analyzed dopamine (DA), serotonin (5-HT) and its metabolites (DOPAC: 3,4-diidroxifenilacetic acid, 5HIAA: 5-hydroxyindoleacetic acid) and the mRNA expression of dopaminergic receptors D1 and D2 (Drd1 and Drd2), DA transporter (Dat), tyrosine hydroxylase (Th), glial cell line-derived neurotrophic factor (Gdnf) and brain-derived neurotrophic factor (Bdnf). The TE in all animals increased with aerobic training. However, the percentage of variation was higher in the LP rats. Before aerobic training, maximal oxygen uptake (VO2max) was different between groups (HP > SP > LP). After aerobic training, the VO2max remained higher in the HP rats compared to LP and SP groups. The VO2max in the LP-TR was higher compared to LP-SED. The ME was higher in all rats submitted to aerobic training when compared to controls. In SED groups, the dopaminergic turnover was higher in HP groups compared to LP and SP. The mRNA expression of Drd2 was higher in LP-SED rats compared to SP-SED and HP-SED animals. The aerobic training increased the dopaminergic turnover in LP and decreased in HP rats. These changes reverted the differences observed 11 in the CPu dopaminergic activity before aerobic training. In the CPu, 6 weeks of aerobic training decreased the mRNA of Drd2 and Dat and increased the mRNA of Gdnf in the LP group. In the HP group, the mRNA of Bdnf decreased with aerobic training. Taken together, our data suggest that the intrinsic capacity to exercise modulates neuroplasticity of dopaminergic system induce by aerobic physical training